Correlation between neuropeptide Y and vitamin D: is it related to body mass index in gender difference? - Sari, Dina Keumala; Ichwan, M; Masyithah, Dewi; Dharmajaya, Ridha; Khatib, Alfi (Hunan Daxue/Hunan University, 2021)
One’s appetite has a role in controlling food intake and maintaining energy balance, but its effect on body metabolism related to obesity is still questionable, especially in the sex difference. This study aimed to determine the correlation between neuropeptide Y and vitamin D and whether it is related to body mass index or not in healthy people and to see differences in gender difference. The goals were to understand orexigenic factors in the brain to be used to understand obesity. The scientific novelty was this study is the first to examine the correlation of brain neuropeptides that affect appetite with vitamin D, see how they are related to obesity, and compare between sexes. This study was a cross-sectional study of healthy males and females aged 18-60 who did not have chronic diseases or metabolic disorders. This research was conducted from April to July 2020 in North Sumatra Province, Indonesia. The parameters examined in this study were 25(OH)D serum levels, neuropeptide Y serum levels, and anthropometric parameters. The statistical analysis performed the correlation was the Spearman test. This study involved 62 study subjects; based on an anthropometric examination, it was found that obesity was more common in the female group than in the male group (p = 0.003). However, serum neuropeptide Y levels were significantly different between male and female groups (p = 0.001). There was also a considerably lower 25(OH)D serum level in the female group than the male group (p = 0.001). There was a positive correlation between neuropeptide Y and 25(OH)D serum levels and a negative correlation between neuropeptide Y and body mass index. The study found significant differences in serum neuropeptide Y levels in male groups but higher body mass index in female groups—many factors affecting obesity in females such as lower 25(OH)D serum level.